DNA methylation analysis of the macrosatellite repeat associated with FSHD muscular dystrophy at single nucleotide level. - Claudia Huichalaf; Stefano Micheloni; Giulia Ferri; Roberta Caccia; Davide Gabellini (PLoS ONE)
Facioscapulohumeral muscular dystrophy (FSHD) is one of the most common inherited diseases of the skeletal muscle. It is characterized by asymmetric muscle weakness and variable penetrance. FSHD is linked to a reduction in copy number of the D4Z4 3.3 kb macrosatellite repeat, located in 4q35. This causes the epigenetic de-repression of FSHD candidate genes leading to disease. Nevertheless, the molecular mechanism responsible for silencing of FSHD candidate genes in healthy subjects is not fully understood. While a role for DNA methylation has been suggested, so far there is limited information regarding the methylation status of the 325 CpGs contained in each D4Z4 unit. Using a human/rodent monochromosomal hybrid cell line containing a single human chromosome 4, we performed an in depth analysis of DNA methylation for the majority of the CpGs inside D4Z4 at single nucleotide level. We found that D4Z4 is not uniformly methylated and that the level of DNA methylation does not correlate with the density of CpG dinucleotides. Moreover, in several D4Z4 regions characterized by near complete methylation, we found specific unmethylated CpGs. These elements are enriched in transcription factor binding sites that could be involved in muscle-specific D4Z4 activity. Our approach also detected differential methylation among different D4Z4 units, suggesting that the D4Z4 array is a mosaic of euchromatic and heterochromatic domains. Finally, we found that DNA methylation and histone de-acetylation are required to maintain FSHD candidate genes repressed. Taken together, our data underscore new players involved in the epigenetic regulation of the FSHD locus that could be targeted for therapeutic purposes.